The Enhanching Profession Mandarin Translation Competence For Employees In Multinational Work Environments - Silvia Siregar, Sheyra; Hanifah Insani, Nur (Majalah Ilmiah UPI YPTK, 2025)
ASEAN Economic Community era has intensified multilingual business communication, particularly the use of Mandarin in multinational companies. This condition highlights the importance of professional Mandarin–Indonesian translation competence for local employees. However, limitations in professional translation skills are still evident, especially in mastering technical terminology and applying contextual translation strategies relevant to workplace demands. This community service program aimed to strengthen profession-oriented Mandarin translation competence among employees of PT LBM Energi Baru Indonesia in Kendal Regency, Central Java. The implementation methods included seminars, workshops, hands-on practice in translating professional documents, and mentoring on translation techniques and strategies, particularly technical terms in chemistry and company administration. Evaluation was conducted through process observation and assessment of participants’ translation performance. The results indicated improvements in participants’ understanding of contextual translation techniques, accuracy in term selection, terminology consistency, and confidence in bilingual workplace communication. Literal translation errors and meaning mismatches decreased after the mentoring sessions. These findings demonstrate that practice-based training is effective in enhancing professional translation competence and is essential for preparing local human resources to meet the demands of global business communication.